Impact of haplo-donor age on transplant outcomes: a comparative analysis of haploidentical vs cord blood transplantation - Takashi Nagayama; Shin-ichiro Fujiwara; Satoshi Nishiwaki; Fumiya Wada; Naoyuki Uchida; Masatsugu Tanaka; Mamiko Sakata-Yanagimoto; Makoto Onizuka; Kazuya Ishiwata; Yuta Hasegawa; Shuichi Ota; Noriko Doki; et al. (Blood Advances)
Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) from HLA-matched donors is the gold standard. However, haploidentical stem cell transplantation using posttransplant cyclophosphamide (PTCY-haplo) and cord blood transplants (CBTs) are alternatives when HLA-matched donors are not available. Using Japanese registry data, we evaluated the impact of haploidentical donor age on posttransplant outcomes by comparing PTCY-haplo and CBT. We analyzed data for 5161 patients aged 16 to 70 years who received their first HSCT for acute leukemia, myelodysplastic syndrome, or chronic myeloid leukemia. Haploidentical donors were categorized as “younger” (aged <40 years) or “older” (aged ≥40 years), and the patients were divided into younger (aged <50 years) and older (aged ≥50 years) cohorts. In the older cohort, PTCY-haplo from younger donors had better overall survival (OS; 55.5% vs 50.8%, P = .006), lower nonrelapse mortality (NRM; 17.3% vs 28.6%, P < .001), and higher relapse rates (33.0% vs 24.9%, P = .017) than with CBT. PTCY-haplo from older donors had comparable OS (44.1% vs 50.8%, P = 1.00), NRM (27.3% vs 28.6%, P = 1.00), and relapse (29.2% vs 24.9%, P = .90) to that with CBT. In the younger cohort, PTCY-haplo from younger and older donors showed OS, NRM, and relapse comparable with CBT. In the older cohort, cumulative incidence of acute graft-versus-host disease (GVHD) was higher with CBT than with PTCY-haplo, regardless of donor age. However, in the younger cohort, acute GVHD was lower in PTCY-haplo from younger donors than with CBT. PTCY-haplo from younger donors to older patients offers better clinical outcomes than CBT.